How to build resilient community energy systems? Lessons from Malawi and Ethiopia - Harshit Vallecha; Mulualem Gebreslassie; Fana Filli; Christopher Hara; Chrispin Gogoda; Amare Assefa; Long Seng To; Joshua Kirshner; Vanesa Castán Broto (Environmental Research: Infrastructure and Sustainability)
This paper defines the notion of realising resilient community energy systems (R-CESs) through community capital to withstand unforeseen natural hazards, climate change induced risks and socio-political disruptions. It evaluates the interrelationship between different stages of CES project implementation with the development of the community’s resilience in the form of social, human, economic, physical and natural capital. This study employs empirical research by carrying out case study analysis of CES projects deployed in risk-prone regions of Malawi and Ethiopia. Three CES projects, two in Malawi and one in Ethiopia, have been examined through qualitative analysis of data collected through semi-structured interviews with CES project stakeholders. Case studies analysed the role of different stakeholders in planning, installation, and operation of projects and the evolution of the community’s resilience during phases of project implementation. In-depth critical analysis of cases demonstrates how a community’s evolved resilience in different forms of community capital enables it to cope with unforeseen shocks/disruptions encountered over the period of CES operation. Comparative analysis of cases proposed the novel R-CES framework defining seven key components of community capital to realise a R-CES in practice. The proposed framework provides recommendations and best practices to CES project developers, managers and community representatives to implement CES projects in a way that strengthens community capital to thus realise a resilient community and sustainable infrastructure.